2021
DOI: 10.4103/jmp.jmp_75_21
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Craniospinal Irradiation – The implementation and Use of Normal Tissue Complication Probability in Comparing Photon versus Proton Planning

Abstract: Purpose: The preferred radiotherapy treatment for medulloblastoma is craniospinal irradiation (CSI). With the aim of developing the potential to reduce normal tissue dose and associated post-treatment complications with photon and proton radiotherapy techniques for CSI. This report aims to carefully compare and rank treatment planning and dosimetric outcomes for pediatric medulloblastoma patients using normal tissue complication probability (NTCP) formalism between photon (three-dimensional confor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…They concluded that the doses to the lens, thyroid gland, lungs, heart, spleen, kidneys, esophagus, and optic nerve were significantly lower in the IMPT group. 19 In our study, the maximum dose to the lens exceeded 10 Gy (RBE), which created dose constraints in our hospital in 4 out of the 8 patients in the PSPT group because of the need to ensure a sufficient dose to the cribriform plate. In contrast, the maximum dose did not exceed the threshold in any of the 16 patients in the IMPT group.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…They concluded that the doses to the lens, thyroid gland, lungs, heart, spleen, kidneys, esophagus, and optic nerve were significantly lower in the IMPT group. 19 In our study, the maximum dose to the lens exceeded 10 Gy (RBE), which created dose constraints in our hospital in 4 out of the 8 patients in the PSPT group because of the need to ensure a sufficient dose to the cribriform plate. In contrast, the maximum dose did not exceed the threshold in any of the 16 patients in the IMPT group.…”
Section: Discussionmentioning
confidence: 83%
“…Giantsoudi et al 18 investigated a simulation study and revealed that the dose conformity of IMPT was better than that of PSPT, and a significant dose decrease was observed in the esophagus. In a similar study, Balasubramanian and Shobana 19 conducted a comparative study of IMPT, intensity modulated RT, helical tomotherapy, and volumetric-modulated arc therapy in 8 patients. They concluded that the doses to the lens, thyroid gland, lungs, heart, spleen, kidneys, esophagus, and optic nerve were significantly lower in the IMPT group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have studied the possibility of sparing the hippocampus and other OARs while performing the WBRT and simultaneous boost with the three planning methods and compare these plans with dosimetric, EUD, and radiobiological models. Balasubramanian et al [22,23] compared photon and proton planning radiobiologically using LKB and Niemierko NTCP models, and they found that the results were reliable for comparing different planning methods.…”
Section: Discussionmentioning
confidence: 99%
“…These new radiotherapy techniques produce significant improvements in dose distribution in the target volume and the junction layer. 3 , 4 However, they also expand the low dose range of irradiation, which may generate severe myelosuppression when the prescribed dose is consistent with that of CSI-CRT. 5 Severe myelosuppression in patients often affects the smooth progress of CSI treatment 6 and also reduces the tumor cure rate, 7 so it has become a hot issue of concern to clinicians.…”
Section: Introductionmentioning
confidence: 99%